The mediating role of innovation between family influence and business performance of public listed family businesses in Malaysia / Chong Wei Ying - Chong, Wei Ying (2014)

(untitled)
Innovation is a sine qua non for many businesses in today’s competitive, complex and capricious environment. Plenty researches have highlighted that innovation is closely linked with business performance. Yet, to date, scant attention has been given to innovation in the world dominant form of business - family business. Even pertaining researches carried out in the past, the focuses are normally on the family versus nonfamily business dichotomy on innovation performance. However, in reality, family influence on business is multidimensional and continuous. The involvement and pattern of family influences vary from business to business. This dissertation seeks to fill these gaps by exploring the links between family influence, innovation and business performance. The study was undertaken in Malaysia context using a sample of 174 public listed family businesses. The data were obtained through questionnaire survey conducted over a period of six months. The study involved three constructs: family influence, innovation and business performance. Family influence was operationalized using the F-PEC scale. There are three important dimensions in F-PEC scale: power, experience and culture. The innovation construct was measured using innovation in product/process and idea generation prevailing in the company. The business performance was measured by family goal performance and financial performance. Data were analyzed using two tests: Statistical Package for the Social Science (SPSS) 20.0 and Structural Equation Modeling (SEM) with AMOS 20.0. Whereas the former test was used in the pilot test to verify the reliability and screened the iv preliminary data, the latter was conducted to explore the direct and indirect effects of family influence on innovation and business performance. Analysis of the structural relationship supports three out of the ten hypotheses. The hypothesized model results provided evidence that not all dimensions in F-PEC scale are statistically significant related with innovation. Among the dimensions in F-PEC scale, only culture is statistically significant related with innovation in family businesses. With regard to the direct effects of family influence on business performance, the study found that none of the dimensions in F-PEC scale is statistically significant related with business performance. Concerning the direct effect of innovation on business performance, as expected, innovation is positively linked with business performance. In the case of mediating effect, this study concluded that the influence of culture on business performance is mediated by innovation. The findings of this study should help both practitioners and academicians understand the link between family influence, innovation and business performance better. It strikes to provide a foundation for ongoing research into family business’ innovation, and the nature related family influence and their management.